Efficacy evaluation of a Haemonchus contortus antigen-containing vaccine (Wirevax®) in sheep in South Africa - Schwan, E.V. (Volker) (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 2014.